ACADEMIC MEDICAL LIBRARIANS IN MALAYSIA: WHAT ROLES DO THEY PLAY? - Santra, Namita (Malaysian Journal of Library and Information Science, 2017)
This study was conducted among academic medical librarians in Malaysia to learn what activities they were engaged in, their awareness of the skills and knowledge required for the emerging roles of medical librarianship and to find out their education and training needs. Face-to-face and telephone interviews were conducted with librarians attached to academic medical libraries in Malaysia. Results indicated that instructional roles had increasingly become part of the librarians’ tasks. Activities that would have granted them some knowledge of the domain or expertise in searching specific medical information was missing. Awareness of the skills and knowledge of the emerging roles was poor. Training and education to specialize in the field was limited. It is recommended that creating opportunities for further training and education can establish a specialist group and improved performance.